Fertility in Bangladesh villages: socio-economic and community differentials - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
Abstract: This report assesses the role of development programme in reducing fertility in rural Bangladesh. Data for this research came from Watch, a demographic and health surveillance system of BRAC covering 70 villages in 10 regions of the country. A total of 9,862 married women of reproductive ages were interviewed that provided their fertility history along with the basic socioeconomic information of the households. Findings reveal that both general and total fertility rates were inverselv associated with age, education, land ownership and socioeconomic status of women. The regional variation in fertility was very high and significant. The credit programme participation played a negative and statistically significant role in reducing both general and total fertility in rural Bangladesh.